Communication as a part of identity of sustainable subjects in fashion - Alena Kusá; Marianna Urmínová (Journal of Risk and Financial Management, 2020)
Sustainability and corporate social responsibility have today become key assets of many successful businesses and corporations. Despite constantly growing environmental awareness, we are still facing the issue of overconsumption in both the textile and fashion industries. This is mainly due to improper marketing communication of sustainable subjects or a rather low level of consumers' awareness of sustainability issues. The main objective of the research is, through the opinions of selected authors and their studies, to compare the results of our own research focusing on Generations Y and Z and dealing with marketing communication of sustainable fashion. As part of the above objective, we attempt to propose the general trend in marketing communication of sustainable subjects. In order to reach this objective, we use the method of description and comparison of opinions of various authors, the analysis of the research questionnaire into the impact of marketing communication of sustainable fashion houses on consumers from Generations Y and Z and its comparison with previous research for the last three years. Thanks to the results of the research, we could observe that tools, media or forms of marketing communication of sustainable fashion producers have certainly changed. The research also provides answers to some of our questions in relation to the general interest of consumers in fashion sustainability, price as a decisive factor in the purchase of sustainable goods and the need for proper education in the field of sustainable fashion or any corresponding forms of marketing communication of sustainable subjects.
Keywords: 330; consumer behaviour; marketing communication; sustainable fashion; corporate identity; education; Generation Y; Generation Z